2007
DOI: 10.1001/archpsyc.64.11.1229
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Impaired Early-Stage Visual Processing to Working Memory Dysfunction in Adolescents With Schizophrenia

Abstract: The P1 amplitude reduction indicates an early visual deficit in adolescents with schizophrenia. Our findings suggest that P1 is of particular relevance for successful WM encoding. Early visual deficits contribute to impaired WM in schizophrenia in addition to deficits in later memory-related processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
139
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(166 citation statements)
references
References 79 publications
24
139
3
Order By: Relevance
“…P100 amplitude was greater under ketamine than under placebo, which went against our prediction that the pattern observed in schizophrenia (8,(10)(11)(12)59,63) would be replicated. There are several potential ways to interpret our unexpected finding .…”
Section: P100 Effectcontrasting
confidence: 61%
“…P100 amplitude was greater under ketamine than under placebo, which went against our prediction that the pattern observed in schizophrenia (8,(10)(11)(12)59,63) would be replicated. There are several potential ways to interpret our unexpected finding .…”
Section: P100 Effectcontrasting
confidence: 61%
“…A large majority of these studies have also shown P1 deficits although eight of the twenty-six did not. The finding of the P1 deficit has been most consistent in our group of studies in chronic patients in New York [7-9, 21, 23, 26, 56] although more recently, a number of other groups have shown similar deficits [16,28,59]. However, only a few of these studies have examined the relationship between these early processing deficits and disease state.…”
Section: Introductionsupporting
confidence: 61%
“…Although these eight studies did not find P1 deficits, as above, the large majority of studies where P1 was measured have. In many of these studies [28] the effect size was very large. All in all, the weight of evidence appears to overwhelmingly favour a robust P1 deficit in patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Several behavioral studies have shown impaired performance in patients with schizophrenia linked to dysfunctional WM encoding (Javitt et al, 1997;Lencz et al, 2003;Lee and Park, 2005). Furthermore, we provided evidence that the event-related potential (ERP) component P100 is of relevance for successful WM encoding in controls and is reduced in adolescent patients with schizophrenia (Haenschel et al, 2007b). WM maintenance deficits in schizophrenia have also been observed both behaviorally (Tek et al, 2002;Badcock et al, 2008) and using functional magnetic resonance imaging (fMRI), especially in the dorsolateral prefrontal cortex (DLPFC) (Cannon et al, 2005;Lee et al, 2008) using spatial delayed response tasks.…”
Section: Introductionmentioning
confidence: 73%
“…Trials with different WM load levels were randomly distributed across sessions with a total of 50 trials obtained per WM load level. The ERP data have been reported previously (Haenschel et al, 2007b).…”
Section: Stimuli and Taskmentioning
confidence: 90%